Determinan Faktor Ambidexterity Inovasi di Instansi Pemerintah untuk Meningkatkan Kinerja Instansi - Kusumawati, Riny; Nasution, Shinta (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2024)
The current issue within government institutions is the lack of efficiency and innovation in public services to enhance competitiveness. Government institutions, as public sector holders, are often perceived as less innovative compared to the private sector. However, innovation in the public sector plays a crucial role in improving efficiency, quality, and public satisfaction. The objectives of this study are: (1) to identify the factors influencing innovation ambidexterity in the Youth and Sports Office (Dispora), (2) to understand how the Dispora manages available resources to support innovation activities, and (3) to explore changes in resource allocation, roles and responsibilities, or technology utilization that support the implementation of innovation ambidexterity. The purpose of this research is to focus on innovation in the underdeveloped public sector, as only a few studies have examined efforts to drive performance-oriented organizational changes. This study employs a quantitative research methodology with a quota sampling technique involving 68 respondents. Data were collected from the Youth and Sports Office as the organizer of the Youth Innovation Summit and West Jawa Innovation Fellowship programs. The results of the PLS-SEM analysis indicate that dynamic balance and exploratory innovation are influenced by structural and relational models. Furthermore, exploratory innovation affects innovation ambidexterity. Thus, enhancing exploratory innovation becomes key to achieving innovation ambidexterity in the context of government institutions. The recommendations from this research provide significant contributions to government institutions in improving existing innovation programs. The Dispora can gain valuable insights and recommendations to enhance the effectiveness, efficiency, and impact of related innovations.